Leg ulcers: atypical presentations and associated comorbidities - Rayner, Robyn; Carville, Keryln; Keaton, Juliet; Prentice, Jenny; Santamaria, Nick (Cambridge Media, 2009)
WoundsWest is an innovative Western Australian (WA) project under Ambulatory Care and Chronic Disease Management Reform undertaken in partnership with the Western Australian Department of Health, Curtin University of Technology and Silver Chain Nursing Association. WoundsWest's Online Wound Management Education Program is a core component of WoundsWest. It involves the interdisciplinary development of an anticipated 16 online wound management education modules, which are designed to assist health professionals and health services to deliver best practice in wound management and reduce preventable wounds and adverse wound management outcomes. The development of these modules involves an extensive search of the literature to ascertain the evidence for best practice. In preparation for the development of the forthcoming online Leg Ulcer Module a considerable number of atypical leg ulcer presentations and associated comorbidities were identified. This paper outlines some of these presentations and comorbidities and reminds health professionals of the need for further diagnostic investigations when leg ulcer signs and symptoms are atypical, or the ulcer fails to heal in an orderly and timely manner.